Investigations of Structural Parameters of ZrN (Bulletin of Pure and Applied Sciences – Physics, 2020)
The present paper discusses the structural properties of ZrN in B1, B2 and B3 phase  by using the hybrid scheme B3LYP as in inbuilt crystal code. The code is based on  well-known theory of the density functional theory. The lattice constant and the bulk  modulus are calculated and compared with the previous investigation